REVIEW OF CHARACTERISTICS AND PROPERTIES OF FE2O3/SIO2 AS WATER POLLUTION PREVENTION - Soerya, Balada; Edianta, Jaya; Lailaturofi'ah, Siti; Ningtyas, Aniendita; Arsyad, Fitri Suryani; Setiabudidaya, Dedi; Sailah, Siti (Indonesian Physical Review, 2022)
The existence of water on earth is very abundant and has a vital role in the source of life for every living creature. In managing water resources, pollution is one of the issues world researchers face. This article reviews the characteristics and methods of synthesizing Fe2O3 and SiO2 materials to prevent water pollution. The strategies administrated antecedently square measure vapor deposition, microemulsion, solvothermal, coprecipitation, sol-gel, and hydrothermal. The formation of fine quality nanoparticles with controlled size associate degreed size distribution square measure typically achieved by selecting an applicable solvent mixture and varied parameters like temperature, pressure, and time interval.